2012
DOI: 10.3324/haematol.2012.071456
|View full text |Cite
|
Sign up to set email alerts
|

Plerixafor and granulocyte colony-stimulating factor for first-line steady-state autologous peripheral blood stem cell mobilization in lymphoma and multiple myeloma: results of the prospective PREDICT trial

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nalone or with chemotherapy, and the potential for toxicities and infection with chemotherapy-based mobilization highlighted the need to develop novel mobilization agents. 6,10 Plerixafor is a novel bicyclam small-molecule that reversibly binds to chemokine receptor CXCR4 and antagonizes the chemokine stromal cell-derived factor-1α (SDF-1α) interaction. 173 Plerixafor is approved by the Food and Drug Administration in combination with G-CSF to mobilize hematopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 14 publications
4
36
0
2
Order By: Relevance
“…Adverse events were mild and acceptable, and comparable with published data on the more commonly used plerixafor/filgrastim combination, 22 and all patients self-injected at Table 3. CD34+ yields and kinetics-study group vs historical controls Plerixafor plus pegfilgrastim patients Pegfilgrastim-alone historical controls…”
Section: Discussionsupporting
confidence: 82%
“…Adverse events were mild and acceptable, and comparable with published data on the more commonly used plerixafor/filgrastim combination, 22 and all patients self-injected at Table 3. CD34+ yields and kinetics-study group vs historical controls Plerixafor plus pegfilgrastim patients Pegfilgrastim-alone historical controls…”
Section: Discussionsupporting
confidence: 82%
“…For the Belgian patients included in this European Compassionate Use Program, a success rate of 64% in a mean of two apheresis sessions has been reported, 20 which is in line with the observation in this registry in the group of patients with known mobilization failure (63%). Plerixafor use in a first mobilization attempt has been described by Russell et al 21 who has reported results of the European multicentre PREDICT trial in which plerixafor was used in first line in all mobilization attempts. Success rate was 96% in a median of 1 day of apheresis (range 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Engraftment is established when the absolute neutrophil count is greater than 500 cells/ dl for three consecutive days or greater than 1,000 cells/dl for one day, and platelets remain greater than 20,000 cells/ dl, independent of platelet transfusions for at least seven days (DiPersio, Stadtmauer, et al, 2009). About three weeks (days +17 to +25) following infusion of HSCs, most acute toxicities, including myelosuppression related to the HDC, have resolved (Russell et al, 2013). Once the patient has no evidence of infection, has demonstrated engraftment, and establishes the ability to maintain oral hydration and nutrition, arrangements can be made for discharge (Pallera & Schwartzberg, 2004).…”
Section: Phase 3: Engraftmentmentioning
confidence: 99%